Transformation of Administrative Management with Artificial Intelligence (AI) Integration in Modern Office Environment through Systematic Journal Review Approach - Ngurah Sanjaya, I Gusti; Ketut Lasmini, Ni; Supiatni, Ni Nyoman; Luh Putu Inten Rumini, Ni; Mas Suryaniadi, Sagung (Yayasan Pendidikan Belajar Berdikari, 2025)
Administrative management has become more efficient with the integration of artificial intelligence (AI), automating repetitive tasks like data processing and document management. This reduces human workload and error rates. AI also supports decision-making by analyzing large datasets and identifying trends that inform strategic planning. However, challenges such as high investment costs, resistance to change, data privacy concerns, and algorithmic bias must be addressed for successful AI implementation, especially in modern office environments where AI is reshaping human roles. This study, Research on AI in Administrative Management: A Systematic Journal Review, uses a Systematic Journal Review methodology to examine both the benefits and challenges of AI integration in administrative tasks. Data was sourced from credible journals and analyzed using descriptive qualitative approaches and thematic synthesis to identify patterns, trends, and gaps in the literature. In conclusion, AI adoption is transforming office administration by enhancing automation and streamlining processes, resulting in cost savings, improved productivity, and timely document management. However, issues such as overreliance on technology, cyber threats, job displacement, and the erosion of human skills pose concerns. With proper planning and training, organizations can minimize these risks and fully leverage AI’s potential.